Determinant Variables of Human Resources Management Practices in Micro and Small Businesses - Pérez-Campdesuñer, Reyner (2021)
Currently, there is little research that delves into the details of human talent management for micro and small companies. Through this research, the aim is to characterize the extent to which human resource management (HRM) practices of micro and small companies in Ecuador differ or resemble the practices of this discipline in medium and large companies. For this purpose, access to information was had on the way in which this management area is developed in 974 representative organizations of the different strata of the universe of companies of the population under study, and on the degree of application of the different functions. In addition, other variables such as the number of workers and the age of the company were evaluated. As a fundamental result, the existence of levels of correlation between the degree of development of the activity and the size and age of the company was established. Likewise, it was found that the level of development of HRM functions, in particular, and of the activity, in general, varies in correspondence with the type of organization.